Effect of Cement Dust Exposure on Total and Differential Count of WBC of Cement Factory Workers - Datta, Arunima; Chowdhury, Raju; Begum, Momtaz; Akhter, Sahin; Akhter, Mahbuba; Barua, Debjane (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Cement is an essential component of construction industry in developed world. Cement dust is one of the major air pollutant and its exposure reported various occupational problems. It has deleterious effects on vital organs. Different study revealed alteration of total and differential count of WBC in cement factory workers. This study was designed to assess effect of cement dust on total and differential count of WBC. Materials and methods: This case control study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram in collaboration with Heidelberg Cement Bangladesh Ltd. Chattogram during the period January 2018 to December 2018. Total 120 male subjects, aged between 20-45 years were included in the study by consecutive sampling method who meets the inclusion criteria. Case group were selected from those who were working at least 2 year in direct contact of cement dust. Control group were selected from office workers of Heidelberg Cement Bangladesh Ltd. and Chittagong Medical College.60 subjects included in each group. A questionnaire along with general information, about present and previous disease, medication and previous job history were filled up by the researcher. Individual’s height and weight were measured, BMI was calculatedand general physical examinations were done. Total 3 ml of venous blood was collected from each subject by trained technician under aseptic precaution. Total and differential count of WBC was estimated in the laboratory by haematology auto-analyzer.After compiling data,statistical analyses were done by using SPSS version Windows 25. For continuous and categorical data Unpaired students’t test and chi–square test were done respectively as test of significance. Results: Significant increase (p<0.001) in eosinophil count was found in Case group workers comparing Control group. Conclusion: The results of this study suggest that occupational exposure to cement dust has deleterious effects on haemopoietic system which is evident by increase eosinophil in cement exposed workers. JCMCTA 2022 ; 33 (2) : 49-54